Analysis of The Effect of Organizational Justice, Worklife Balance on Employee Engagement and Turnover Intention - Mulang, Hastuti (Manunggal Halim Jaya, 2022)
The problem that managers or leaders face in an organization or company to compete in ensuring the organization's survival is the existence of employees as human resource assets. Turnover intentions arise in employees when there is perceived injustice and work-life balance in the company because needs are not met. This study uses a quantitative approach, with the type and source of data in this study being primary data in the form of a questionnaire given to the entire sample of 70 employees of PT. BSB–Kalla Group. Data analysis used a quantitative method with SEM using the SmartPLS. The study results found that employee engagement cannot be a mediating variable on organizational justice and work-life balance on turnover intention. The direct effect shows positive and significant results from the two independent variables on the dependent variable. Indirectly mediated by employee engagement, the two independent variables negatively affect the dependent variable on the turnover intention. Based on the results of the research and discussion described previously, it can be concluded in this study that turnover intention is determined by the application of organizational justice to the company and creates a work-life balance for each employee through employee engagement as a mediating variable.